مجلة جامعة الملك عبدالعزيز-علوم البحار 2012
DOI: 10.4197/mar.23-1.7
|View full text |Cite
|
Sign up to set email alerts
|

Microtextures of Quartz Grain Surface from Recent Sedimentary Environments along Al-Khowkhah- Al-Mokha Coastal Area, Southern Red Sea, Yemen

Abstract: Scanning electron microscopy (SEM) analyses of quartz grains from Recent sedimentary environments such as beach, coastal duns,sabkha and wadi deposits in the Al-Khowkhah and Al-Mukha coastal area along southern Red Sea, Yemen, revealed variations in surface textures. Results of this study reveals the existence of distinguished surface features that reflect the effect of mechanical and chemical actions on the quartz grains. Quartz grains of beach, coastal dune and wadi deposits show significant abundance of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Many researchers have emphasized that microtextures on quartz grain surfaces can be used to identify different sedimentary environments and modes of transport mechanisms [1][2][3][4][5][6][7][8][9]. The microtextures of quartz sand grains can provide valuable information about the various processes acting on grains during transportation and after deposition [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have emphasized that microtextures on quartz grain surfaces can be used to identify different sedimentary environments and modes of transport mechanisms [1][2][3][4][5][6][7][8][9]. The microtextures of quartz sand grains can provide valuable information about the various processes acting on grains during transportation and after deposition [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the beach sediments of Al-Khowkhah were derived largely from the igneous and volcanic rocks outcropping to the east of the studied area. [4] utilized microtextures on quartz grains from the Al-Khowkhah and Al-Mokha coastal areas to the south of Al-Hodeidah, to clarify the relationship between the various recent sedimentary environments. However, none of these studies utilized microtextures on quartz grains from the Al-Khowkhah beach area of southern Hodeidah to examine sediment provenance.…”
Section: Introductionmentioning
confidence: 99%